Sexual History Taking and Empathic Opportunity: A Communication Skills Workshop - Carla Lupi; Nicolette Hopson (Association of American Medical Colleges, 2010)
Abstract Introduction This workshop contains tools to review basic medical encounter communications skills as applied to sexual history taking, and to introduce the advanced skills of both handling of emotional silence ("the potential empathic opportunity") and communicating during intimate examination and procedures. The workshop consists of a series of five skits that serve as a springboard for facilitated discussion. The skits may either be acted by a faculty member serving as the physician and either a second faculty member or student acting as the patient, or shown in the provided video files. Methods The five skits depict sequential portions of a single office visit for "Ruby," a patient known to this physician who presents with a "yeast infection" and a significant hidden agenda. The facilitator will show the scenes (or act them out) one at a time, following each scene with the questions: "What did the doctor do right/well? What did s/he do wrong/incorrectly?" Built into each scene are examples of highly effective communications techniques and major communications errors. Other portions of the scenes provoke mixed reactions from observers/students. The facilitator guide contains instructions for leading the introduction of the workshop as well as scene-by-scene guides to facilitate discussion, and questions regarding the various communication skills depicted. Results This workshop has been used with every block of third-year students on the core obstetrics and gynecology clerkship at the University of Miami Miller School of Medicine for more than 4 years. Blocks number 10-27 students though the average number of students is around 20. Student ratings have been consistently "excellent" among 90% or more of respondents. It has also been presented to OB/GYN residents and family practice residents. Discussion Responses to specific skills depicted in the skits may vary, depending on how they are acted, providing a rich variety of discussion if the facilitator chooses to act in real time rather than use the videos. A student can be trained within 15 minutes to play the role of the patient. It is important to emphasize that she maintain the silence required in scene III to exploit the teaching points of the potential empathic opportunity, as novice actors have difficulty maintaining this silence.